DTF Study and Biological Activity of Some Methylxanthines - Salihović, Mirsada; Huseinović, Šukrija; Špirtović-Halilović, Selma; Osmanović, Amar; Dedić, Alema; Ašimović, Zilha; Završnik, Davorka (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
The main aim of this study is to show the research results of learning outcomes on thermal physics that have gained a group of first-year chemistry students in the fall semester of the academic 2013-2014 year. In this paper is described the use of a questionnaire to explore chemistry freshmen capacity to which they achieve their understanding of thermal physics concepts they learn within the chemistry and physics courses during the first study year. A used questionnaire contains 20 questions including a question on which the 94 study participants had the task to give their explanations related to a selected question. Research results show that knowledge about thermal equilibrium, the first law of thermodynamics and other relations among physical quantities students did not acquire in a way to present their scientific literacy developed enough at university learning outcomes level. Students need some additional instructions to find their pathways from pre-instructional alternative concepts to learn the scientific concepts through new working sessions enriched with experiments and demonstrations by instructors, teaching assistants as well as a group of students actively involved in learning on thermal physics subject matter.